The management of precast concrete production and usage in Singapore - Ong, Ting Guan. (2008)
Due to the rapid growth of technology in the building industry and the increasing emphasis on higher productivity in construction, precast concrete construction is gaining more recognition during the last few years and is regarded as an economic, structurally sound and architecturally versatile building system. By adopting prefabrication, it will certainly help to upgrade the construction skills of the contractors as well as improve the overall productivity and buildability of buildings. Besides, it will also offer a new dimension to building professionals to exercise their creativity and innovativeness in the building industry.